Reevaluation of Late Pleistocene loess profiles at Remizovka (Kazakhstan) indicates the significance of topography in evaluating terrestrial paleoclimate records. Issue 3 (15th February 2018) - Sprafke, Tobias; Fitzsimmons, Kathryn E.; Grützner, Christoph; Elliot, Austin; Marquer, Laurent; Nigmatova, Saida
Abstract: We report on a loess-paleosol sequence (LPS) near Remizovka, located in the northern Tian Shan piedmont of southeastern Kazakhstan. This site represents a key record for Late Pleistocene climatic fluctuations at the intersection of major northern hemisphere climate subsystems. This paper develops a synthesized dataset of previous conflicting studies at Remizovka by characterizing their (paleo)topographic context, which had remained previously overlooked. Digital elevation models, satellite images, and archival photography characterize recent topographic developments. Two well-developed pedocomplexes, which we investigate in detail and date by luminescence mark the paleotopography during Marine Oxygen Isotope Stage (MIS) 5. Peak dust accumulation rates here occurred during the middle MIS 5 and MIS 4/early MIS 3. These are partially comparable with records from neighboring regions, but not in phase with global ice volume records. This discrepancy may be related to a distinct regional environmental response to larger-scale climatic drivers and local topographic influences on dust deposition patterns. Our findings confirm the potential of the LPS Remizovka to provide high-resolution paleoclimate data for the Late Pleistocene. The three-dimensional stratigraphic reconstruction reinforces the caution required to correctly interpret loess formation processes prior to their interpretation as paleoclimate archives, and provides guidelines for a more suitable approach.